The pace and tempo of running in the analysis of the performances of the top hurdlers at the Olympic Games in Paris - Ogandzhanov A. L.; Samoylov G. V.; Salamatov M. B.; Tsyplenkova E. S. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the key kinematic features that contribute to the success of the world's top male hurdlers in the 110m hurdles race, we conducted a thorough examination of the performances at the Paris Olympics.